Evaluation of Information Technology Governance Maturity Using COBIT 2019: Study of a Telecommunication Company - Muhamad Rendi Novrian; Dazki, Erick (P3M Politeknik Negeri Bengkalis, 2025)
The development of information technology drives the need for effective IT governance, especially in the telecommunications sector, which faces challenges such as 5G, Iot, and strict regulations. This research aims to evaluate the maturity level of IT governance at PT Wahana Sukses Makmur and identify gaps against the COBIT 2019 standard to support business strategy. Quantitative methods were used through structured questionnaires to 15 respondents selected by purposive sampling, as well as internal document analysis. The data was analysed using the COBIT 2019 toolkit and triangulated to increase validity. The results show that IT governance maturity is at levels 1 and 2, far from the level 4 target in domains APO13, APO07, and DSS01. Recommendations include the formulation of risk-based information security policies, the development of an IT HR competency roadmap based on organisational needs, and continuous digitisation of operational processes. This research faced limitations in the number of respondents and access to certain internal documents, which affected the depth of analysis. The contribution of the research lies in the holistic evaluative approach based on COBIT 2019 in the real context of the Indonesian telecommunications sector, as well as practical implications in strategic decision-making related to IT governance.